State, forest and community: challenges of democratically decentralizing forest management in the Centre-West Region of Burkina Faso - Bouda, H.; Savadogo, P.; Tiveau, D.; Ouédraogo, B. (2009)
This study examines challenges associated with early stages of decentralizing the administration and management of forest resources in the Centre-West Region of Burkina Faso. It is based on fi eldwork using rapid rural appraisal, focus group discussions and interviews with key stakeholders, methodology to explore the strengths and weaknesses of participatory forest management, and the main issues and challenges involved in these processes. The study found that a shift of administrative authority to the local level will not guarantee transparency and good governance in the forest sector unless measures are taken to remove challenging obstacles. The central government is still reluctant to decentralize a revenue-generating sector such as forestry and the involvement of civil society remains weak. Decentralization also results in a plethora of confl icts at the local level as new responsibilities and opportunities arise with the devolution of new powers to the community. Decentralization of forest management will probably remain a work in progress for the foreseeable future. Thus, we recommend the introduction or reinforcement of participatory development programs through local dialogue with various stakeholders and an investigation of new policy and institutional arrangements that may promote equitable forest management. Copyright 2009 John Wiley & Sons, Ltd and ERP Environment